High-damping composite material as well as preparation method and application thereof
The high damping composite material, featuring a porous framework filled with a dynamically intercrosslinked polymer fluid, addresses the challenge of maintaining mechanical stability and wide frequency/temperature ranges, achieving superior damping performance and energy dissipation.
Patent Information
- Application Number
- CN202510000837.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing high molecular weight damping materials struggle to maintain both wide frequency and temperature ranges while ensuring mechanical stability, leading to potential structural instability and safety issues in applications such as aerospace and automotive industries.
A high damping composite material comprising a porous framework filled with polymer fluid, where the porous framework and polymer fluid ratio ranges from 5:50 to 50:95, and the polymer fluid has a dynamic intercrosslinked network structure, providing enhanced damping performance across 10^-2 to 10^3 rad/s frequency and -30 to 200°C temperature ranges.
The composite material achieves a damping coefficient greater than 0.3 with a storage modulus change ratio of 4-10, ensuring stable mechanical properties and effective energy dissipation across a wide frequency and temperature range, addressing the limitations of traditional damping materials.
Smart Images

Figure CN119708849A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer damping materials, and in particular to a high-damping composite material and a preparation method and application thereof. Background Art
[0002] Polymer damping materials, also known as polymer vibration absorbing materials, are functional materials that can utilize the unique viscoelastic relaxation mechanism of polymers to convert mechanical vibrations into heat energy and dissipate it, thereby preventing or reducing the destructive effects of mechanical vibrations on components. Therefore, polymer damping materials are widely used in many fields such as aerospace, transportation, and precision instruments.
[0003] With the development trend of electronic devices and engineering equipment towards high power, strong drive and long cycle, ultra-high or ultra-low frequency vibration and noise will be generated, which requires polymer damping materials to have a wide effective damping range. Although traditional damping materials can achieve high damping capacity in a wide temperature range and wide frequency range by introducing multiple polymer relaxation mechanisms, they usually lead to drastic changes in mechanical properties, which inevitably damages structural stability and safety of use. Therefore, it is urgent to develop polymer composite materials with both stable mechanical properties and high damping properties to adapt to a wider range of application scenarios and improve the safety and application cycle of the structure.
[0004] CN110951023A discloses a polymer damping material that can be repaired at room temperature, and its preparation method and application, including the following preparation raw materials: polyol, isocyanate, chain extension crosslinking agent and solvent; the polyol includes amino-terminated polyol or hydroxyl-terminated polyol; the molar ratio of the polyol to isocyanate is (1.1-1.3):1; the crosslinking degree of the polymer damping material that can be repaired at room temperature is 5-30%. However, when this technical solution is applied, the temperature range corresponding to the loss factor greater than 0.3 is only 15-77°C at the widest. However, in some technical fields, such as when the automobile engine is working, the local temperature can reach 100°C and above. The polymer damping material prepared in this technical solution will lose its performance due to the incompatibility of the temperature range, and unexpected failures will occur, thereby affecting the use of the device and may even cause some safety accidents.
[0005] CN117467278A discloses a high damping silicone rubber and its preparation method, wherein the raw materials include silicone rubber monomer, crosslinking agent, secondary bond-containing polymer and linear polymer fluid. The silicone rubber provided by this technical solution includes a permanently chemically crosslinked polymer network, which ensures the ability of the silicone rubber material to maintain its shape and reversibly deform; at the same time, the secondary bond-containing polymer and the linear polymer fluid provide two energy dissipation mechanisms for the silicone rubber material, so that the silicone rubber material exhibits excellent damping performance in a wide frequency band or temperature range. That is, the silicone rubber prepared by this technical solution has excellent damping performance in the temperature range of -30-120°C or 10 -2 -10 2 rad / s frequency range, the damping coefficient is above 0.3. However, in some technical fields, such as rockets, missiles, artificial satellites in aerospace, or optical instruments, medical equipment, semiconductor manufacturing equipment in precision instruments, etc., the devices involved require a higher effective damping frequency, which needs to be above 100 rad / s. Therefore, the silicone rubber of this technical solution cannot meet the requirements, and it is necessary to develop polymer damping materials with a higher effective damping frequency; more importantly, the high damping silicone rubber prepared by this technical solution has a storage modulus change factor of greater than or equal to 10.
[0006] Based on the above-mentioned prior art, there are technical problems that need to be solved urgently, such as the polymer damping material in the prior art has a wide temperature range and a wide frequency range but cannot have stable mechanical properties. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a high damping composite material, which comprises a porous framework and a polymer fluid filling the pores of the porous framework; The mass ratio of the porous framework to the polymer fluid is (5-50): (50-95); Rheological tests were performed using a rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 4-10, and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is -30-200℃, and the damping coefficient is greater than 0.3.
[0008] Furthermore, the rheometer is an Anton Paar flat plate rheometer.
[0009] Furthermore, the storage modulus variation factor of the high damping composite material is the ratio of the modulus obtained by high frequency testing to the modulus obtained by low frequency testing; wherein the frequency of the high frequency testing is 1000 rad / s, and the frequency of the low frequency testing is 0.01 rad / s.
[0010] Furthermore, the porous frame has a foam structure or a honeycomb structure.
[0011] Furthermore, the pore diameter of the foam structure is 10-1000 μm.
[0012] Furthermore, the pore diameter of the honeycomb structure is 10-1000 μm.
[0013] Furthermore, the porosity of the porous framework is 50-98%.
[0014] Further, the porosity = (1-relative density) × 100%; Where relative density = apparent density of porous framework / real density of porous framework; Apparent density of porous framework = mass of porous framework / overall volume of porous framework; The real density of the porous framework is the density of the raw material of the porous framework itself.
[0015] Furthermore, the material of the porous frame includes one or more of metal rubber, polyurethane, and ethylene-vinyl acetate copolymer (EVA).
[0016] Furthermore, the material of the metal rubber is stainless steel.
[0017] Furthermore, the polymer fluid has a network structure, and the network structure is a dynamically cross-linked polymer fluid network or a composite network composed of fluid polymers with different weight-average molecular weights.
[0018] Furthermore, the raw materials for preparing the polymer fluid include one or more of a dynamic crosslinking agent and a linear polymer fluid.
[0019] Furthermore, the mass ratio of the dynamic crosslinking agent to the linear polymer fluid is (0-50): (50-90).
[0020] Furthermore, the dynamic cross-linking agent is polyborosiloxane.
[0021] Furthermore, the weight average molecular weight of the polyborosiloxane is 800-5000.
[0022] Furthermore, the linear polymer fluid is linear polysiloxane.
[0023] Furthermore, the linear polysiloxane is in a liquid state at room temperature.
[0024] Furthermore, the linear polysiloxane includes one or more of polydimethylsiloxane, polyphenylmethylsiloxane, and polydiethylsiloxane; The linear polysiloxane can also be composed of the same linear polysiloxane with different weight average molecular weights.
[0025] Furthermore, the linear polysiloxane is preferably polydimethylsiloxane.
[0026] Furthermore, the weight average molecular weight of the linear polymer fluid is 50,000-300,000.
[0027] Furthermore, the weight average molecular weight of the linear polymer fluid is preferably 60,000-260,000.
[0028] Furthermore, the molecular weight of the polydimethylsiloxane is one or more of 63,000, 139,000, 140,000, and 260,000.
[0029] Furthermore, the molecular weight of the polyphenylmethylsiloxane is one or more of 40,000, 160,000, and 250,000.
[0030] Furthermore, the molecular weight of the polydiethylsiloxane is one or more of 10,000, 90,000, and 240,000.
[0031] The present invention also provides a method for preparing a high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of a polymer fluid; Step 2: introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, and then drying to obtain the high damping composite material.
[0032] Furthermore, the preparation process of the precursor solution in step 1 is: dispersing one or more of the dynamic crosslinking agent and the linear polymer fluid in an organic solvent according to a mass ratio, and stirring evenly to obtain the precursor solution.
[0033] Furthermore, the mass ratio of the organic solvent to the solute in the precursor solution is (0.5-5):1.
[0034] Furthermore, the organic solvent is one or more of toluene, n-hexane, xylene, and tetrahydrofuran.
[0035] Furthermore, the stirring temperature is room temperature.
[0036] Furthermore, in step 2, the drying temperature is 50-100° C. and the drying time is 24-48 hours to dry and volatilize the organic solvent.
[0037] Furthermore, in step 2, the drying temperature is 60-70° C. and the drying time is 36-48 hours.
[0038] Furthermore, the number of times of immersion and drying in step 2 is greater than or equal to 1 time, until the pores of the porous framework are filled with the polymer fluid.
[0039] Furthermore, the dynamic cross-linking agent in step 1 is polyborosiloxane, and the polyborosiloxane is obtained by direct purchase or preparation; The preparation method of polyborosiloxane comprises the following steps: mixing boric acid, an alcohol solvent and hydroxyl-terminated polydimethylsiloxane to carry out a dehydration condensation reaction to obtain polyborosiloxane.
[0040] Furthermore, the mass ratio of the boric acid to the alcohol solvent is 1:(30-60).
[0041] Furthermore, the mass ratio of the boric acid to the alcohol solvent is preferably 1:50.
[0042] Furthermore, the mass ratio of the boric acid to the hydroxyl-terminated polydimethylsiloxane is 1:(30-70).
[0043] Furthermore, the mass ratio of the boric acid to the hydroxyl-terminated polydimethylsiloxane is preferably 1:40.
[0044] Furthermore, the alcohol solvent is methanol.
[0045] Furthermore, the weight average molecular weight of the hydroxyl-terminated polydimethylsiloxane is 500-5000.
[0046] Furthermore, the weight average molecular weight of the hydroxyl-terminated polydimethylsiloxane is preferably 4200.
[0047] Furthermore, the temperature of the dehydration condensation reaction is room temperature, and the reaction time is 0.5-3h.
[0048] Furthermore, the reaction time is preferably 1.5 h.
[0049] Furthermore, the reaction is carried out under stirring conditions, and the stirring speed is 1000-1500 rpm.
[0050] Furthermore, the preparation method of the polyborosiloxane is specifically as follows: according to the mass ratio, boric acid is first dissolved in the alcohol solvent to obtain an alcohol solution of boric acid, and then the hydroxyl-terminated polydimethylsiloxane is added to the alcohol solution of boric acid, and the reaction is carried out under stirring. After the dehydration condensation reaction is completed, centrifugation is carried out to obtain the polyborosiloxane.
[0051] Furthermore, the centrifugal speed is 5000 rpm and the centrifugal time is 5 min.
[0052] The present invention also provides a polymer damping material product, which is prepared from the high damping composite material.
[0053] Furthermore, the polymer damping material products include but are not limited to sealing rubber, precision instrument shock-absorbing pads, sports shoe soles, and human protection equipment.
[0054] Furthermore, the human body protection equipment includes but is not limited to knee pads and bulletproof vests.
[0055] The beneficial effects of the present invention are: 1. The present invention provides a high damping composite material, which comprises a porous frame and a polymer fluid filling the pores of the porous frame; the porous frame, on the one hand, serves as a mechanical support to maintain mechanical stability; on the other hand, through capillary force, it produces a mutual physical effect with the network structure of the polymer fluid, thereby limiting the cold flow of the fluid; at the same time, the whole chain relaxation of the polymer fluid network structure ensures that the high damping composite material prepared by the present invention has high energy dissipation (damping) in a wide frequency and wide temperature range. The rheological test is carried out using a rheometer under the condition of a shear strain of 0.5%. The high damping composite material has a storage modulus change factor of 4-10, and an effective damping frequency range of 10 -2 -10 3 rad / s, the effective damping temperature range is -30-200℃, and the damping coefficient is greater than 0.3; 2. The polymer fluid has a network structure, which is a dynamically cross-linked polymer fluid network or a composite network composed of fluid polymers with different weight average molecular weights (without a dynamic cross-linking agent). Both types of polymer fluid network structures can be -2 -10 3 rad / s wide frequency and a wide temperature range of -30-200°C to complete multiple relaxations, thereby achieving high damping performance of the composite material, and the composite material prepared by the present invention has a damping coefficient greater than 0.3 within the above temperature and frequency range, and at the same time, the change multiple of its storage modulus does not exceed 10 times; 3. When the network structure of the polymer fluid is a dynamically cross-linked polymer fluid network, the essence of using a dynamic cross-linking agent is that the boron atoms in polyborosiloxane have empty orbitals and can act as acceptors of unshared electron pairs on oxygen atoms, thereby forming a non-bonded complex, causing physical cross-linking between molecules, and further strengthening the interaction between the porous framework and the polymer fluid; when the network structure of the polymer fluid is a composite network composed of fluid polymers with different weight-average molecular weights, due to the different entanglement properties of molecular chains of different lengths, molecular chain entanglement networks of different degrees are formed; therefore, the polymer fluid can achieve mutual cooperation with the porous framework in the microstructure, thereby achieving a good damping effect in a wider temperature and frequency range; 4. The high-damping composite material provided by the present invention overcomes the problems of low damping coefficient, narrow effective frequency / temperature range, poor mechanical stability, etc. of traditional polymer damping materials. It is a high-damping, wide temperature range, wide frequency band, and highly stable composite material, which is expected to be widely used in the fields of precision instrument protection, body health protection, noise control, equipment vibration reduction, etc.; and the present invention also provides a preparation method of the composite material, which has a simple process, low cost, and is easy to achieve large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a schematic diagram of the composition structure of the high damping composite material of Example 2 of the present invention; Figure 2 This is a microscopic image of the microstructure of the high damping composite material of Example 2 of the present invention; Figure 3 This is a diagram showing the modulus-angular frequency dependence of the high damping composite material of Example 2 of the present invention; Figure 4 This is a graph showing the dependence of the loss factor (damping coefficient) on the angular frequency of the high damping composite material according to Example 2 of the present invention; The names of the labels in the figure are: 1. Porous framework; 2. Polymer fluid. DETAILED DESCRIPTION
[0057] Example 1 The present embodiment first provides a method for preparing polyborosiloxane, comprising the following steps: first dissolving boric acid in methanol at a mass ratio of boric acid to methanol of 1:50 to obtain a boric acid methanol solution, then adding the hydroxyl-terminated polydimethylsiloxane to the boric acid methanol solution at a mass ratio of boric acid to hydroxyl-terminated polydimethylsiloxane of 1:40, wherein the weight-average molecular weight of the hydroxyl-terminated polydimethylsiloxane is 4200, reacting at room temperature at a stirring speed of 1000 rpm for 1.5 hours, and after the dehydration condensation reaction is completed, centrifuging at a speed of 5000 rpm for 5 minutes to obtain the polyborosiloxane.
[0058] The dynamic crosslinking agent involved in the following examples is the polyborosiloxane prepared in this example.
[0059] Example 2 This embodiment provides a high damping composite material, such as Figure 1-2 As shown, the high damping composite material comprises a porous framework 1 and a polymer fluid 2 filling the pores of the porous framework; In this embodiment, the porous framework 1 is a foam structure with a pore diameter ranging from 300 to 600 μm and a porosity of 78%, and is made of polyurethane; the polymer fluid 2 has a network structure, and the network structure is a dynamically cross-linked polymer fluid network. The raw materials for preparing the polymer fluid include the dynamic cross-linking agent polyborosiloxane prepared in Example 1, and polydimethylsiloxane with a weight average molecular weight of 140,000 as a linear polymer fluid; Therefore, in this embodiment, the mass ratio of the porous framework of the polyurethane foam structure, polyborosiloxane, and polydimethylsiloxane with a weight average molecular weight of 140,000 is 10:45:45.
[0060] This embodiment also provides a method for preparing the above-mentioned high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of polymer fluid 2: dispersing 45 parts of the dynamic crosslinking agent polyborosiloxane prepared in Example 1 and 45 parts of polydimethylsiloxane with a weight average molecular weight of 140,000 as linear polymer fluids in an organic solvent toluene, and stirring at room temperature to obtain the precursor solution; the mass ratio of the organic solvent to the solute in the precursor solution is 1:1; Step 2, introducing the precursor solution into the porous framework 1 by impregnation and filling the pores of the porous framework, the porous framework 1 generates a mutual physical interaction with the network structure of the precursor solution by capillary force, restricting its cold flow, and then drying to obtain the high damping composite material; The drying temperature is 60° C. and the drying time is 48 h. In this embodiment, the precursor solution is introduced into the porous framework 1 multiple times by an immersion-drying cycle until the pores of the porous framework are filled after the second cycle.
[0061] Rheological tests were carried out using an Anton Paar plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 6.7, and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is 0-200℃, and the damping coefficient is greater than 0.3, that is, no damping coefficient less than or equal to 0.3 is found in the entire temperature scanning range.
[0062] Among them, the modulus-angular frequency relationship curve obtained by Anton Paar flat plate rheometer is as follows: Figure 3 As shown. Where G' is the storage modulus, G'' is the loss modulus, G'' / G' is the loss factor, and the calculation results are shown as Figure 4 As shown, Figure 3-4The results show that within the wide frequency range of the test, the storage modulus and loss modulus of the high damping composite material change only slightly, while the loss factor (damping coefficient) remains above 0.3, indicating that the high damping composite material has both mechanical stability and high damping performance.
[0063] Example 3 This embodiment provides a high damping composite material, which includes a porous framework and a polymer fluid filling pores in the porous framework; In this embodiment, the porous framework is a honeycomb structure with a pore diameter ranging from 500 to 1000 μm and a porosity of 90%, and is made of polyurethane; the polymer fluid has a network structure, and the network structure is a composite network composed of fluid polymers with different weight-average molecular weights, and the raw materials for preparing the polymer fluid include polydimethylsiloxane with weight-average molecular weights of 63,000, 139,000, and 260,000 as linear polymer fluids; Therefore, in this embodiment, the mass ratio of the porous framework of the polyurethane honeycomb structure and the polydimethylsiloxane having weight average molecular weights of 63,000, 139,000 and 260,000 respectively is 10:30:30:30.
[0064] This embodiment also provides a method for preparing the above-mentioned high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of a polymer fluid: dispersing 30 parts of polydimethylsiloxane with weight average molecular weights of 63000, 139000 and 260000 respectively as linear polymer fluids in an organic solvent toluene, and stirring at room temperature to obtain the precursor solution; the mass ratio of the organic solvent to the solute in the precursor solution is 2.5:1; Step 2, introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, the porous framework generates a mutual physical interaction with the network structure of the precursor solution by capillary force, restricting its cold flow, and then drying to obtain the high damping composite material; The drying temperature is 60° C. and the drying time is 48 h. In this embodiment, the precursor solution is introduced into the porous framework multiple times by an immersion-drying cycle until the pores of the porous framework are filled after the fourth cycle.
[0065] Rheological tests were carried out using an Anton Paar plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 5.9, and the effective damping frequency range was 10 -2 -10 2 rad / s, the effective damping temperature range is 0-175℃, and the damping coefficient is greater than 0.3, that is, no damping coefficient less than or equal to 0.3 is found in the entire temperature scanning range.
[0066] Example 4 This embodiment provides a high damping composite material, which includes a porous framework and a polymer fluid filling pores in the porous framework; In this embodiment, the porous framework is a foam structure with a pore diameter ranging from 500 to 900 μm and a porosity of 90%, and the material is metal rubber, specifically stainless steel rubber; the polymer fluid has a network structure, and the network structure is a dynamically cross-linked polymer fluid network. The raw materials for preparing the polymer fluid include the dynamic cross-linking agent polyborosiloxane prepared in Example 1, and polydimethylsiloxane with a weight average molecular weight of 140,000 as a linear polymer fluid; Therefore, in this embodiment, the mass ratio of the porous frame of the metal rubber foam structure, polyborosiloxane, and polydimethylsiloxane with a weight average molecular weight of 140,000 is 50:25:25.
[0067] This embodiment also provides a method for preparing the above-mentioned high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of a polymer fluid: dispersing 25 parts of the dynamic crosslinking agent polyborosiloxane prepared in Example 1 and 25 parts of polydimethylsiloxane with a weight average molecular weight of 140,000 as a linear polymer fluid in an organic solvent toluene, and stirring at room temperature to obtain the precursor solution; the mass ratio of the organic solvent to the solute in the precursor solution is 1:1; Step 2, introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, the porous framework generates a mutual physical interaction with the network structure of the precursor solution by capillary force, restricting its cold flow, and then drying to obtain the high damping composite material; The drying temperature is 60° C. and the drying time is 48 h. In this embodiment, the precursor solution is introduced into the porous framework multiple times by an immersion-drying cycle until the pores of the porous framework are filled after the third cycle.
[0068] Rheological tests were carried out using Anton Paar's plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 8.0, and the effective damping frequency range was 10 -1 -10 1 rad / s, the effective damping temperature range is -20-50℃, and the damping coefficient is greater than 0.3, that is, the damping coefficient is not less than or equal to 0.3 in the entire temperature scanning range.
[0069] Example 5 This embodiment provides a high damping composite material, which includes a porous framework and a polymer fluid filling pores in the porous framework; In this embodiment, the porous framework is a foam structure with a pore diameter ranging from 700 to 900 μm and a porosity of 90%, and the material is ethylene-vinyl acetate copolymer (EVA); the polymer fluid has a network structure, and the network structure is a composite network composed of fluid polymers with different weight-average molecular weights, and the raw materials for preparing the polymer fluid include polyphenylmethylsiloxane with weight-average molecular weights of 40,000, 160,000, and 250,000 as linear polymer fluids; Therefore, in this embodiment, the mass ratio of the porous framework of the ethylene-vinyl acetate copolymer foam structure and the polyphenylmethylsiloxane having weight average molecular weights of 40,000, 160,000 and 250,000 respectively is 10:30:30:30.
[0070] This embodiment also provides a method for preparing the above-mentioned high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of a polymer fluid: dispersing 30 parts of polyphenylmethylsiloxane with weight average molecular weights of 40,000, 160,000 and 250,000 respectively as linear polymer fluids in an organic solvent of toluene, and stirring at room temperature to obtain the precursor solution; the mass ratio of the organic solvent to the solute in the precursor solution is 2.5:1; Step 2, introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, the porous framework generates a mutual physical interaction with the network structure of the precursor solution by capillary force, restricting its cold flow, and then drying to obtain the high damping composite material; The drying temperature is 60° C. and the drying time is 48 h. In this embodiment, the precursor solution is introduced into the porous framework multiple times by an immersion-drying cycle until the pores of the porous framework are filled after the third cycle.
[0071] Rheological tests were carried out using Anton Paar's plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 8.9, and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is -30-180℃, and the damping coefficient is greater than 0.3, that is, the damping coefficient is not less than or equal to 0.3 in the entire temperature scanning range.
[0072] Example 6 This embodiment provides a high damping composite material, which includes a porous framework and a polymer fluid filling pores in the porous framework; In this embodiment, the porous framework is a foam structure with a pore diameter ranging from 700 to 900 μm and a porosity of 90%, and the material is ethylene-vinyl acetate copolymer (EVA); the polymer fluid has a network structure, and the network structure is a composite network composed of fluid polymers with different weight-average molecular weights, and the raw materials for preparing the polymer fluid include polydiethylsiloxane with weight-average molecular weights of 10,000, 90,000, and 240,000 as linear polymer fluids; Therefore, in this embodiment, the mass ratio of the porous framework of the ethylene-vinyl acetate copolymer foam structure and the polydiethylsiloxane having weight average molecular weights of 10,000, 90,000 and 240,000 respectively is 10:30:30:30.
[0073] This embodiment also provides a method for preparing the above-mentioned high damping composite material, comprising the following steps: Step 1, preparing a precursor solution of a polymer fluid: dispersing 30 parts of polydiethylsiloxane with weight average molecular weights of 10,000, 90,000 and 240,000 respectively as linear polymer fluids in an organic solvent of toluene, and stirring at room temperature to obtain the precursor solution; the mass ratio of the organic solvent to the solute in the precursor solution is 2.5:1; Step 2, introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, the porous framework generates a mutual physical interaction with the network structure of the precursor solution by capillary force, restricting its cold flow, and then drying to obtain the high damping composite material; The drying temperature is 60° C. and the drying time is 48 h. In this embodiment, the precursor solution is introduced into the porous framework multiple times by an immersion-drying cycle until the pores of the porous framework are filled after the third cycle.
[0074] Rheological tests were carried out using an Anton Paar plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 9.8, and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is -30-160℃, and the damping coefficient is greater than 0.3, that is, the damping coefficient is not less than or equal to 0.3 in the entire temperature scanning range.
[0075] Comparative Example 1 Compared with Example 2, this comparative example omits the porous frame and provides a composite material. The specific preparation method is as follows: Step 1, preparing a precursor solution: dispersing 50 parts of the dynamic crosslinking agent polyborosiloxane prepared in Example 1 and 50 parts of polydimethylsiloxane with a weight average molecular weight of 140,000 in an organic solvent toluene, and stirring at room temperature to obtain the precursor solution; Step 2: pour the precursor solution into a mold, and then dry it to obtain the high damping composite material; wherein the drying temperature is 60° C. and the drying time is 48 hours.
[0076] Rheological tests were carried out using Anton Paar's plate rheometer under a shear strain of 0.5%. The storage modulus of the composite material changed by a multiple of 530 and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is 0-200℃, and the damping coefficient is greater than 0.3.
[0077] Comparative Example 2 Compared with Example 2, the polymer fluid having a dynamically cross-linked polymer fluid network was omitted in this comparative example, and the polyurethane foam was used as a porous framework and dried at a drying temperature of 60° C. for 48 hours.
[0078] Rheological tests were performed using an Anton Paar plate rheometer under a shear strain of 0.5%. The storage modulus of the porous frame varied by a multiple of 2.5, the effective damping frequency range was 0 rad / s, and the effective damping temperature range was 0°C.
[0079] Comparative Example 3 The high damping silicone rubber in Example 1 of CN117467278A was prepared.
[0080] Rheological tests were performed using an Anton Paar plate rheometer under a shear strain of 0.5%. The storage modulus of the high damping silicone rubber varied by a multiple of 12, and the effective damping frequency range was 10 -2 -10 2 rad / s, the effective damping temperature range is -30-121℃.
[0081] The test results of the embodiment and the comparative example are compared in Table 1: Table 1 Comparison of properties of composite materials prepared in Examples and Comparative Examples
[0082] According to the data in Table 1, it can be seen that the composite materials prepared in Examples 2-6 have a small change in storage modulus over a wide frequency and temperature range, reflecting a significantly high mechanical stability; at the same time, their damping coefficient reaches above 0.3, showing excellent damping performance. Comparative Example 1 omits the addition of a porous frame, and the modulus change multiple of the obtained material within the test range is nearly 100 times that of Examples 2-6; Comparative Example 2 omits the addition of a dynamically cross-linked fluid matrix, and the damping performance of a single frame is extremely poor, and the loss factor does not reach above 0.3; Comparative Example 3 is a composite material prepared using existing technology, and the modulus change multiple of the obtained material within the test range is also higher than that of Examples 2-6.
[0083] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A high damping composite material, characterized in that: The high damping composite material comprises a porous framework and a polymer fluid filling the pores of the porous framework; The mass ratio of the porous framework to the polymer fluid is (5-50): (50-95); Rheological tests were performed using a rheometer under a shear strain of 0.5%. The storage modulus of the high damping composite material varied by a multiple of 4-10, and the effective damping frequency range was 10 -2 -10 3 rad / s, the effective damping temperature range is -30-200℃, and the damping coefficient is greater than 0.
3.
2. The high damping composite material according to claim 1, characterized in that: The porous frame has a foam structure or a honeycomb structure.
3. The high damping composite material according to claim 2, characterized in that: The material of the porous frame includes one or more of metal rubber, polyurethane, and ethylene-vinyl acetate copolymer.
4. The high damping composite material according to claim 1, characterized in that: The polymer fluid has a network structure, which is a dynamically cross-linked polymer fluid network or a composite network composed of fluid polymers with different weight-average molecular weights.
5. The high damping composite material according to claim 4, characterized in that: The raw materials for preparing the polymer fluid include one or more of a dynamic crosslinking agent and a linear polymer fluid.
6. A method for preparing the high damping composite material according to any one of claims 1 to 5, characterized in that: The steps include: Step 1, preparing a precursor solution of a polymer fluid; Step 2: introducing the precursor solution into the porous framework by impregnation and filling the pores of the porous framework, and then drying to obtain the high damping composite material.
7. The method for preparing the high damping composite material according to claim 6, characterized in that: The preparation process of the precursor solution in step 1 is: dispersing one or more of the dynamic crosslinking agent and the linear polymer fluid in an organic solvent according to a mass ratio, and stirring to obtain the precursor solution.
8. The method for preparing the high damping composite material according to claim 6, characterized in that: The drying temperature in step 2 is 50-100° C. and the drying time is 24-48 hours.
9. A polymer damping material product, characterized in that: The high damping composite material is prepared from the high damping composite material according to any one of claims 1 to 5.
10. The polymer damping material product according to claim 9, characterized in that: The polymer damping material products include sealing rubber, precision instrument shock-absorbing pads, sports shoe soles, and human body protection equipment.
Citation Information
Patent Citations
Honeycomb core composite structural material and preparation method thereof
CN104057658A
Aerogel-based energy-absorbing material as well as preparation method and application thereof
CN115748238A
Vibration damping composite material
CN1266447A